2007
DOI: 10.1016/j.jinteco.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Technology spillover through trade and TFP convergence: 135 years of evidence for the OECD countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
141
0
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(166 citation statements)
references
References 34 publications
9
141
0
12
Order By: Relevance
“…As can be clearly seen, developed nations uniformly imported its actual amount of Science Research of and beyond what these nations produce themselves. This is certainly consistent with the conclusion of the literature (Madsen 2007;Keller 2002;Eaton and Kortum 1996). Among these developed nations, the U.S. stands out both in terms of growth rate and absolute dollar value.…”
Section: Logistics Globalizationsupporting
confidence: 91%
See 1 more Smart Citation
“…As can be clearly seen, developed nations uniformly imported its actual amount of Science Research of and beyond what these nations produce themselves. This is certainly consistent with the conclusion of the literature (Madsen 2007;Keller 2002;Eaton and Kortum 1996). Among these developed nations, the U.S. stands out both in terms of growth rate and absolute dollar value.…”
Section: Logistics Globalizationsupporting
confidence: 91%
“…Madsen showed that the U.S., Japan, and the Scandinavian countries experienced approximately 300% GFP growth due to such technology spillovers (Madsen 2007). Keller estimated that benefits derived from foreign R&D in the same industry are on the order of 50% to 95% of the productivity of old R&D (Keller 2002).…”
Section: Shanghai's Import Trade In Producer Servicesmentioning
confidence: 99%
“…This argument has been confirmed by recent works using more sophisticated, trade-related weights (Lumenga-Neso et al, 2005), different measures of knowledge capital (Bottazzi and Peri, 2007;Madsen, 2007, and, or alternative mechanism of knowledge propagation (Lee, 2006 andMendi, 2007). It should be however emphasized that the differential impact between foreign and domestic R&D might be reducing over time (Guellec and van Pottelsberghe, 2004) and such other factors as human capital and institutional characteristics may be influential for productivity growth (see Engelbrecht, 1997, Frantzen, 2000and Coe et al, 2008.…”
mentioning
confidence: 77%
“…The distance can be reduced by R&D, which have been shown as having an innovative character in OECD countries (Howitt, 2000;Griffith et al, 2003;Kneller, 2005). Research intensity reduces the distance to the frontier as proved by Griffith et al (2004), Kneller (2005), Kneller and Stevens (2006) and Madsen (2007Madsen ( , 2008a. Zachariadis (2003Zachariadis ( , 2004 and Madsen (2008b) have empirically proved that R&D intensity has positive effects on TFP growth, then on the distance to the frontier, for OECD countries.…”
Section: Higher Growth and Backwardnessmentioning
confidence: 96%